Implementasi Perbankan Syariah Di Malaysia Dan Indonesia - Satria Darma (Journal Economy and Currency Study (JECS), 2021)
This study aims to analyze the implementation of Islamic banking in Malaysia and Indonesia. This research uses exploratory study method, descriptive analysis in analyzing secondary data related to these problems. The results show that the difference in product diversity and Islamic bank contracts in the two countries is due to several factors such as the economic system adopted by a country, the school of thought or school of thought used by the majority of people in each country, the position of Islamic banks in the law and the approach to law. selected product development.